Single-cell RNA-seq analysis reveals that immune cells induce human nucleus pulposus ossification and degeneration - Guo, Song; Yan, Meijun; Li, Xinhua; Zhang, Shuya; Liu, Zhong; Li, Kewei; Liu, Pengcheng; Liu, Yanbin; Sun, Guixin; Fu, Qiang (Frontiers in Immunology, 2023)
Background and aims Determining the transcriptomes and molecular mechanism underlying human degenerative nucleus pulposus (NP) is of critical importance for treating intervertebral disc degeneration (IDD). Here, we aimed to elucidate the detailed molecular mechanism of NP ossification and IDD using single-cell RNA sequencing.Methods Single-cell RNA-seq and bioinformatic analysis were performed to identify NP cell populations with gene signatures, biological processes and pathways, and subpopulation analysis, RNA velocity analysis, and cell-to-cell communication analysis were performed in four IDD patients. We also verified the effects of immune cells on NP ossification using cultured NP cells and a well-established rat IDD model.We identified five cell populations with gene expression profiles in degenerative NP at single-cell resolution. GO database analysis showed that degenerative NP-associated genes were mainly enriched in extracellular matrix organization, immune response, and ossification. Gene set enrichment analysis showed that rheumatoid arthritis signaling, antigen processing and presentation signaling were activated in the blood cell cluster. We revealed that stromal cells, which are progenitor cells, differentiated toward an ossification phenotype and delineated interactions between immune cells (macrophages and T cells) and stromal cells. Immune factors such as TNF-α, CD74 and CCL-3 promoted the differentiation of stromal cells toward an ossification phenotype in vitro. Blocking TNF-α with a specific inhibitor successfully reversed NP ossification and modified NP morphology in vivo.Our study revealed an increase in macrophages and T cells in degenerative NP, which induced stromal cell differentiation toward an ossification phenotype, and contributed to the identification of a novel therapeutic target to delay IDD.